2004
DOI: 10.1021/je034136z
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Vapor Liquid Equilibrium for Binary 2-Methylpropene + Methanol to Butanol Systems

Abstract: Vapor-liquid equilibria measured with a static apparatus are reported for binary mixtures of 2-methylpropene and the following C1-C4 alcohols at the corresponding temperatures: methanol (323.15 K), ethanol (323.15 K), 2-propanol (323.15 K), 2-butanol (323.15 K), and 2-methyl-2-propanol (313.15 K and 322.77 K). Measured pTz (pressure-temperature-total composition) data were reduced to liquid-and vapor-phase compositions using Barker's method. Binary interaction parameters were optimized for the Legendre polynom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…On the basis on the Legendre polynomial fit, it is located at x 1 = 0.8857, T = 364.5 K, and p = 1631.7 kPa. The azeotropic behavior of isobutene + methanol was also found by Ouni et al No other mixtures showed azeotropic behavior at the experimental conditions.
4 Activity coefficients composition diagram of ○, isobutene + methanol; ×, isobutene + 1-propanol; +, isobutene + 2-propanol; ▵, iso-butene + 2-butanol; and, isobutene + 2-methyl-2-propanol at 364.5 K.
…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…On the basis on the Legendre polynomial fit, it is located at x 1 = 0.8857, T = 364.5 K, and p = 1631.7 kPa. The azeotropic behavior of isobutene + methanol was also found by Ouni et al No other mixtures showed azeotropic behavior at the experimental conditions.
4 Activity coefficients composition diagram of ○, isobutene + methanol; ×, isobutene + 1-propanol; +, isobutene + 2-propanol; ▵, iso-butene + 2-butanol; and, isobutene + 2-methyl-2-propanol at 364.5 K.
…”
Section: Resultssupporting
confidence: 83%
“…The uncertainties in the correlated densities were less than 1.0 % for 2-methylpropane, methanol, 1-propanol, 2-propanal, and 2-methyl-2-propanol and less than 3.0 % for 2-butanol. The derivation of the maximum error for the injected mole amount is presented in detail in refs and , and only the resulting equation is presented here. The theoretical maximum error for an injection is presented in eq 1: …”
Section: Error Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…1 were used. The literature study led to the conclusion that measurements were needed for six binary systems, TBA +: -2, 4, 4-trimethyl-1-pentene [12,15]; -2-methylpropene [16]; -cis-2-butene [17]; -trans-2-butene [18]; -2-methylpropane; -n-butane.…”
Section: Methodsmentioning
confidence: 99%
“…The automated static total pressure apparatus The setup of the static total pressure apparatus and the experimental procedure are described in detail in the article by Uusi-Kyyny et al [6]. The description of the automation of the apparatus can be found in Ouni et al [7]. The equilibrium cell (total volume of 103.33 cm 3 ) was immersed in a water bath (approximately 70 dm 3 in volume).…”
Section: Apparatus and Proceduresmentioning
confidence: 99%